2017
DOI: 10.26480/msm.01.2017.10.14
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and antimicrobial resistance of Listeria monocytogenes isolated from raw milk and dairy products

Abstract: Listeriosis is a severe foodborne disease commonly caused by eating contaminated food with the Listeria species. A large variety of foods, especially dairy foods and ready-to-eat products, can support the growth of pathogens. Outbreaks of listeriosis have been related with milk, cheese, vegetable salads, and meat products, and fatality rates are typically around 20% due to listeriosis. The Centers for Disease Control and Prevention evaluates that 2500 infections and more than 500 deaths are related with lister… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 16 publications
0
17
1
1
Order By: Relevance
“…A study carried out in France showed that only 1.27% human isolates out of 4816 clinical L. monocytogenes resisted the effects of antibiotics tested [20]. Notwithstanding, a growing number of antibiotic-resistant L. monocytogenes are continually documented [1,4]. Naturally occurring resistance to fosfomycin, thirdgeneration cephalosporin and first-generation quinolones have also been documented [21].…”
mentioning
confidence: 99%
“…A study carried out in France showed that only 1.27% human isolates out of 4816 clinical L. monocytogenes resisted the effects of antibiotics tested [20]. Notwithstanding, a growing number of antibiotic-resistant L. monocytogenes are continually documented [1,4]. Naturally occurring resistance to fosfomycin, thirdgeneration cephalosporin and first-generation quinolones have also been documented [21].…”
mentioning
confidence: 99%
“…Chinese medicine treatment of perimenopausal syndrome with kidney deficiency pathogenesis theory (Liu, 2012, Yang and Zhou, 2012), women into the perimenopausal period, kidney qi deficiency, red any two losses, lack of refined gas, menstrual disorders, as well as menopause, and accompanied by a series of symptoms, such as fanre, insomnia, more dreams. Kidney deficiency is the root cause of perimenopausal syndrome (Zhang and Miao, 2011, Gohar et al, 2017). Recent studies have shown that the drug for kidney yang have estrogen-like effects, on perimenopausal syndrome have a better therapeutic effect (Wei and Miao, 2013), and no side effects and contraindications.…”
Section: Discussionmentioning
confidence: 99%
“…What we need to be concerned about is that women's perioperative prevention is particularly important, in the treatment of perimenopausal syndrome at the same time, should fully reflect the traditional Chinese medicine “treatment did not occur disease” thinking, take preventive measures. To avoid low-level Chinese medicine treatment of perimenopausal syndrome experimental and clinical research, under the guidance of traditional Chinese medicine theory, combined with traditional Chinese medicine technology and methods to strengthen scientific research and experimental design, unified standardized dialectical system, to find the objective of the disease differentiation indicators, the establishment of standardized index system, improve the scientific, objectivity and reliability of Chinese medicine for perimenopausal syndrome (Gohar et al, 2017, Jamal et al, 2017). Raspberry as a traditional nourishing kidney medicine, in China has thousands of years of use history, researchers from the raspberry separation of terpenoids, flavonoids, alkaloids, coumarins and other ingredients, and the preliminary pharmacological screening was carried out for the isolated compounds, in the anti-tumor, anti-aging, scavenging free radicals and other aspects of a clear activity.…”
Section: Introductionmentioning
confidence: 99%
“…Current treatment of ischemic brain disease mainly use chemical drugs for treatment, but there are also serious side effects and other shortcomings. In recent years, under the principle of blood circulation and heat detoxification, Chinese medicine in the clinical treatment of cerebral ischemia has played a huge role (Li et al, 2013, Gohar et al, 2017).…”
Section: Discussionmentioning
confidence: 99%